Efficacy of bleomycin application on periungual warts after treatment with ablative carbon dioxide fractional laser: a pilot study. (18th May 2020) - Suh, Joong Heon; Lee, Soo Kyung; Kim, Myoung Shin; Lee, Un Ha
Abstract: Background: Treating periungual warts is a therapeutic challenge. Treatments are often ineffective and may cause complications including permanent nail changes, pain, and scaring. Translesional bleomycin delivery via the multipuncture technique is now reported. Objective: To investigate the efficacy and safety of bleomycin solution (1 U/mL) after ablative fractional carbon dioxide (CO2 ) laser for treating periungual warts. Methods: Warts were treated with ablative CO2 fractional laser, after which bleomycin was applied. Patients were treated every 2 weeks until the lesions disappeared. Treatment was discontinued if adverse events occurred or the patient wanted to stop. Results: Seventeen patients (11 women, mean age 16.23 years) with a total of 38 warts were enrolled from May 2017 to Aug 2018. Twenty-six lesions (68.4%) achieved complete clearance; three (7.8%) had excellent partial response (>75% improvement). The warts clearing completely did not recur over the follow-up period of 6 months. No significant long-term adverse effects occurred. One lesion showed postinflammatory hyperpigmentation, resolving within 1 month; five patients (29%) had short-term localized moderate pain after treatment. Conclusions: Bleomycin solution after ablative fractional CO2 laser is effective and safe to treat periungual warts. Further large controlled studies are necessary to validate effectiveness and find an optimal regimen.